Diversity of aquatic macrophytes in Balili River, La Trinidad, Benguet, Philippines as potential phytoremediators - JONES T NAPALDET; INOCENCIO JR. E BUOT (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Napaldet JT, Buot JR IE. 2019. Diversity of aquatic macrophytes in Balili River, La Trinidad, Benguet, Philippines as potential phytoremediators. Biodiversitas 20: 1048-1054.  Phytoremediation, an emerging, low-cost, aesthetically pleasing technology, is now being eyed for restoration of Balili River, Philippines. But first, there is a need to identify plants ideal for its phytoremediation. Macrophytes in the main stream, Bolo Creek and Mamaga Creek of Balili River were inventoried in this study with focus on determining macrophytes that were local, dominant (=fast growing), have high biomass and deep root systems – traits ideal for phytoremediation. A total of 38 species of macrophytes under 37 genera and 19 families were inventoried. This number is much higher than the previous inventory which recorded only 9 species. Consequently, diversity indices recorded in this study is much higher. The difference could be attributed to the time of sampling wherein the previous inventory was done in July, a rainy month, in contrast with this in April, the summer month at which the river is at its lowest level. At this period, much of the littoral zone is exposed for colonization of plants known to be easily dispersed and germinate such as Asteraceae species. In terms of species richness, family Asteraceae was the most represented with 11 species but in terms of dominance, the story was different. Dominant macrophytes of Balili River were species of family Poaceae (Pennisetum purpureum, Eleusine indica and Cynodon dactylon), Amaranthaceae (Amaranthus spinosus and Alternanthera sessilis), Solanaceae (Solanum americanum) and Commelinaceae (Commelina diffusa). Local macrophytes with potential for phytoremediation were P. purpureum, E. indica, A. spinosus and S. americanum.